2022
DOI: 10.2147/opth.s365618
|View full text |Cite
|
Sign up to set email alerts
|

Myopia: An Increasing Problem for Medical Students at the University of Gondar

Abstract: Purpose The purpose of this study was to assess the prevalence and associated factors of myopia among medical students at the University of Gondar College of Medicine and Health Sciences, Northwest Ethiopia. Patients and Methods Institution-based cross-sectional study was conducted at the University of Gondar College of Medicine and Health Sciences from June 20 to August 15, 2021. A simple random sampling technique with proportional allocation was used to select 492 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 47 publications
(53 reference statements)
0
12
1
Order By: Relevance
“…An initial search produced retrieved 9617 articles (Figure 1). Removal of duplicates and application of selection criteria reduced the number of articles reporting myopia in near work to 78 studies [2,[13][14][15]19,[26][27][28][29][30][31][32][33][34]. All studies were written in English except one in French [85] and one in Italian [30].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…An initial search produced retrieved 9617 articles (Figure 1). Removal of duplicates and application of selection criteria reduced the number of articles reporting myopia in near work to 78 studies [2,[13][14][15]19,[26][27][28][29][30][31][32][33][34]. All studies were written in English except one in French [85] and one in Italian [30].…”
Section: Resultsmentioning
confidence: 99%
“…All studies used autorefractometry for the diagnosis of myopia aiming to calculate the refractive error based on spherical equivalent (SE = sphere + cylinder/2). Most studies used cycloplegia, except 16 studies, mostly on adults [15,31,32,46,47,49,50,55,56,66,67,71,73,78,79,88]. Seventeen studies quantified axial length [15,38,39,44,59,60,64,79,83,84,87,90,[92][93][94], and two studies reported perceptions of visual fatigue [26,97].…”
Section: Methods To Measure Myopiamentioning
confidence: 99%
See 3 more Smart Citations